Teachers’ Perception about Alignment of Components of National Curriculum of Islamiat Grade I to VIII, in Pakistan - Bhatti, Nargis; Chaudhary, Abdul Ghafoor (Pakistan Languages and Humanities Review, 2023)
Purpose of this study was to evaluate the quality and effectiveness of Single National Curriculum of Islamiat Grade 1 to VIII in Pakistan by examining the alignment of its components and objective achievements. Data was collected from teachers of Islamiat who implement it and face difficulties during this process. The mix methodology was utilized in the study as, both qualitative and quantitative research methods were used. Quantitative method was used for collecting data by a questionnaire on rating scale, to know teachers ‘views about alignment of its components, weaknesses, flaws and shortcoming. Qualitative data also was collected from teachers by using open ended question in questionnaire to get views and suggestions in detail regarding alignment of components of curriculum, its gaps, flaws and suggestions to improve it. Finding and results of the study show that 70 % teachers are not satisfied about alignment of its components, particularly about alignment of teaching methods with learning outcomes. Teachers suggested that single national curriculum should be improved more according to the needs of present digital era by aligning its components with learning outcomes particularly teaching methods should be modern and effective to achieve its learning outcomes.